The illiquidity of water markets - Javier Donna; Jose-Antonio Espin-Sanchez (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2013)
In 1966, the irrigation community in Mula (Murcia, Spain) switched from a market (auction), which had been in place in the town for over 700 years, to a system of fixed quotas with a ban on trading, to allocate water from the town's river. We present a model, in which farmers face liquidity constraints to explain why the change took place. We show that water demand will be underestimated if liquidity constraints are present. We use a dynamic demand model and data from the market period to estimate the parameters of the model. We estimate both the demand for water and the financial constraints of the farmers, thus obtaining unbiased estimates. In our model, markets achieve the first-best allocation only in the absence of liquidity constraints. In contrast, the quota achieves the first-best allocation only if farmers are homogeneous in productivity. We compute welfare under both institutions using the estimated parameters. We find that the quota is more efficient than the market. This result implies that one should be cautious in advocating for water markets, especially in developing areas where liquidity constraints might be a concern.
Keywords: D02; D53; G14; Q25; 330; Institutions; Financial Markets; Market Efficiency; Water